Single-electron tunneling PbS/InP heterostructure nanoplatelets for synaptic operations - Jarschel, Paulo Felipe, 1985- (2021)
Agradecimentos: P.F.J., J.H.K., and J.X. thank the support from NSF CMMI 1530547, AFOSR FA9550-19-1-0355, and ARO W911NF-14-2-0075. The study was also financially supported by the European Community’s H2020 Program (grant no. PITN-GA-2016-722176, "Indeed" Project), the EQUIPEX programs Excelsior (grant no. ANR-11-EQPX-0015) and Tempos (grant no. ANR-10-EQPX-0050), and the RENATECH network. We are grateful to D. Pavlidis and G. Dambrine for initiating and enabling the France–USA collaborations. We thank X. Wallart for the XPS analysis